Novel study on investigating the mechanical, microstructure morphological, and dry sliding wear characteristics of grey cast iron GG25 with copper additions for valve guides in internal combustion engine - Singh, Baljeet; Singh Grewal, Jasmaninder; Kumar, Rajeev; Sharma, Shubham; Kumar, Abhinav; Mohammed, Kahtan A.; Awwad, Fuad A.; Khan, M. Ijaz; Ismail, Emad A. A. (Frontiers in Materials, 2024)
Introduction: The performance functionality efficacy of the engine’s valve train assembly is considerably affected by the valve guide. Material selection is impacted by the prolonged operational lifespan of engines, which favours casting and machining materials such as cast iron. The intent of this study is to examine the dry sliding characteristics of GG25 cast iron with copper additives. Discovering the ways in which variations in load and sliding velocity impact wear characteristics is of paramount significance. Methods: The research entailed the examination of wear characteristics across various environmental conditions. Loads were varied at 30 N, 40 N, and 50 N while maintaining a 1 m/s velocity constant. In the same manner, sliding velocities of 0.5 m/s, 1 m/s, and 2 m/s were varied while a constant load of 30 N was maintained. Experimental techniques were carried out at ambient temperature. Throughout the investigations, frictional forces and the coefficient of friction were also determined. The wear mechanisms of samples that had become deteriorated or worn-out were examined by employing a scanning electron microscope when combined with EDX analysis. Results: A rise in the normal load from 30 N to 40 N led to a twofold rise in wear losses, measuring 417 microns as compared with 222 microns previously. The range of wear losses observed at moderate speeds (0.5 m/s–1 m/s) was 133–222 microns. Conversely, the maximum wear loss observed was 1,226 microns at elevated sliding velocities of 2 m/s, in contrast to 617 microns at higher normal loads of 50 N. Additionally, the research discovered that normal load is more pronounced when both loading and speed are moderate, whereas sliding speed becomes more substantial when both are raised, culminating to higher wear losses. Discussions: In summary, the research highlights the considerable effect that normal load and sliding speed have on the prevalence of wear losses. In conditions of moderate loading and velocity, the influence of normal load is more significant. However, as sliding accelerates, it becomes the predominant factor. An analysis of frictional forces as well as the coefficient of friction indicated that under loading conditions of 30 N–50 N, the friction coefficient raised from 0.238 to 0.43. The wear mechanisms, as discerned via scanning electron microscopy and EDX analysis, underscored the considerable impact of increased sliding velocity on wear loss in comparison to conditions of higher loading.